Genome‐Wide Association Study Identifies First Locus Associated with Susceptibility to Cerebral Venous Thrombosis - Ken‐Dror, Gie; Cotlarciuc, Ioana; Martinelli, Ida; Grandone, Elvira; Hiltunen, Sini; Lindgren, Erik; Margaglione, Maurizio; Duchez, Veronique Le Cam; Triquenot, Aude Bagan; Zedde, Marialuisa; Mancuso, Michelangelo; Ruigrok, Ynte M.; et al. (Annals of neurology, 2021)
Objective Cerebral venous thrombosis (CVT) is an uncommon form of stroke affecting mostly young individuals. Although genetic factors are thought to play a role in this cerebrovascular condition, its genetic etiology is not well understood. Methods A genome‐wide association study was performed to identify genetic variants influencing susceptibility to CVT. A 2‐stage genome‐wide study was undertaken in 882 Europeans diagnosed with CVT and 1,205 ethnicity‐matched control subjects divided into discovery and independent replication datasets. Results In the overall case–control cohort, we identified highly significant associations with 37 single nucleotide polymorphisms (SNPs) within the 9q34.2 region. The strongest association was with rs8176645 (combined p = 9.15 × 10−24; odds ratio [OR] = 2.01, 95% confidence interval [CI] = 1.76–2.31). The discovery set findings were validated across an independent European cohort. Genetic risk score for this 9q34.2 region increases CVT risk by a pooled estimate OR = 2.65 (95% CI = 2.21–3.20, p = 2.00 × 10−16). SNPs within this region were in strong linkage disequilibrium (LD) with coding regions of the ABO gene. The ABO blood group was determined using allele combination of SNPs rs8176746 and rs8176645. Blood groups A, B, or AB, were at 2.85 times (95% CI = 2.32–3.52, p = 2.00 × 10−16) increased risk of CVT compared with individuals with blood group O. Interpretation We present the first chromosomal region to robustly associate with a genetic susceptibility to CVT. This region more than doubles the likelihood of CVT, a risk greater than any previously identified thrombophilia genetic risk marker. That the identified variant is in strong LD with the coding region of the ABO gene with differences in blood group prevalence provides important new insights into the pathophysiology of CVT. ANN NEUROL 2021;90:777–788